Educational Justice for Diversified Nepali Children - Koirala, Bidya Nath (Journal of Education and Research, 2008)
Contradictions are the lived realities of the human beings. They are more so with the people of Nepal who live with multiplicities, modernities, and post-modernities. These multiplicities have come from different roots such as language diversities; caste diversities; class diversities; religious pluralities; ascribed, described, and aspirant gender roles; lived and intended power relations with “hierarchicals” caste groups and communal ethnic groups; and pedagogical variations that grew out in the country and that we imported from the West. ! is indicates that we have pluralities to be managed from different lenses. Reflection on personal back up, putting legs on others’ shoes, listening to others, and creating mosaic are some of the measures that are to be nurtured if we want to ensure educational justice to the diverse groups of people. DOI: http://dx.doi.org/10.3126/jer.v1i0.7947 Journal of Education and Research 2008, Vol. 1, No. 1, pp. 13-20